Bentuk Solidaritas Sosial Masyarakat Suku Pakpak Muslim: Kelompok Minoritas di Kota Medan - Rany Masiytah Ujung; Irwansyah Irwansyah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Social solidarity among minority communities in heterogeneous urban settings must be actively maintained to preserve social cohesion amid modernization. This study examines the forms of social solidarity practiced by the Muslim Pakpak community in Medan City through Émile Durkheim’s Theory of Social Solidarity. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and documentation involving three purposively selected informants. Data were analyzed using the Miles and Huberman interactive model and validated through source and method triangulation. The findings indicate that solidarity is sustained through two interconnected foundations: religious activities and kinship ties. Clan-based pengajian and Mutual Aid Associations (Serikat Tolong-Menolong) facilitate silaturahmi, information exchange, and collective support, while the marga, beru, and bere-bere kinship system strengthens mutual trust and gotong royong beyond immediate family relationships. These practices reflect the coexistence of mechanical solidarity rooted in shared ethnic identity and organic solidarity developed through social interaction in a heterogeneous urban environment. The study concludes that social solidarity serves as a collective strategy for preserving social cohesion and sustaining the cultural identity of the Muslim Pakpak minority in the face of modernization and declining youth participation.